Електрографічний друк: технологія, обладнання, матеріали - Григор’єв, О. В.; Вовк, О. В.; Катречко, Д. А.; Брильова, А. С. (ТОВ «Видавництво Ліра-К», 2025)
The main technical indicators of modern electrophotographic equipment are analyzed: printing technology, printing format, printing speed; image resolution, media density, color, toner type. This allows us to justify the most appropriate use of this or that equipment for printing various printing products.
Keywords: електрографічний друк; printing format